Effect of Ethanol Extract from Kepel Leaves (Stelechocarpus burahol (Bl.) Hook F. & Th.) on Confluence and Viability of Primary Mouse (Mus musculus) Neuronal Cells - Harjanti, Fitria Nungky; Hanifah, Lil (Program Study of Biology, Science and Technology Faculty, UIN Maulana Malik Ibrahim Malang, 2025)
Kepel (Stelechocarpus Burahol (Bl.) Hook F. Th.), a plant indigenous to Indonesia, is popular for its various benefits, including anti-hyperuricemia, xanthine oxidase inhibition, anti-implantation, anticancer, antiseptic, anti-inflammatory, and antioxidant properties. However, its potential as a neuroprotective agent is not well understood. Therefore, this study aims to investigate the confluence and viability of primary mouse neurons following the administration of ethanol extract from Kepel (Stelechocarpus burahol (Bl.) Hook F. Th.) leaves. Primary neuron cell cultures were divided into four treatment groups: NT (without treatment), T1 (50 µL of Kepel leaf extract), T2 (75 µL of Kepel leaf extract), and T3 (100 µL of Kepel leaf extract). After 48 hours of incubation, culture confluence and viability were assessed. This study approved that the ethanol extract of Kepel leaves did not significantly affect confluence compared to the non-treated group, but cell viability increased when treated with the Kepel leaf extract compared to the non-treated group.